The prevalence of Candida albicans from oral cavity in patients with HIV seropositive hemophiliacs - Usami, Takeshi; Ohsuka, Shinji; Masuda, Koji; Ueda, Minoru (Journal of Japanese Society of Dentistry for Medically Compromised Patient, 1995)
The mucosae of thirty-seven patients with hemophilia of our outpatients clinic were examined clinically by means of cultivation using Microstix-Candida ® to determine the presence of Candida albicans. Eighteen (48.6%) out of thirty-seven men were seropositive for human immunodeficiency virus (HIV). The other nineteen patients were HIV seronegative. Five out of eighteen (27.8%) HIV seropositive and one out of nineteen (5.3%) HIV seronegative patients had culture-confirmed presence of C. albicans. In the former group, colonization of C. albicans was significantly more frequent in subjects with lymphocytopenia, CD4+ cell deleption, reversed CD4/CD8 rate and elevated DMF index. We did not find the relationship, on the other hand, between score of OHI-S and prevalence of C. albicans from oral cavity. Our findings indicate that oral candidiasis occurs in HIV infection as a result of C. albicans over-growth, and conclude that clinician should be aware of importance of cooperation with dentists and management of dental hygiene.